2020
DOI: 10.3390/jcm9061874
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Multimodal Complex Treatment (PD-MCT): Analysis of Therapeutic Effects and Predictors for Improvement

Abstract: Parkinson’s disease Multimodal Complex Treatment (PD-MCT) is a multidisciplinary inpatient treatment approach that has been demonstrated to improve motor function and quality of life in patients with Parkinson’s disease (PD). In this study, we assessed the efficacy of PD-MCT and calculated predictors for improvement. We performed a prospective analysis in a non-randomized, open-label observational patient cohort. Study examinations were done at baseline (BL), at discharge after two-weeks of inpatient treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 75 publications
(93 reference statements)
6
19
1
Order By: Relevance
“…This corresponds to an absolute reduction of −9.55 points, which is above the minimal clinically important difference for improvement of −3.25 points and is correspondingly clinically significant [ 11 ]. This is in line with earlier studies showing improvement of motor function after PD-MCT [ 4 , 5 , 6 ]. We found that improvement of MDS-UPDRS III after PD-MCT in patients with PD is more likely to occur in patients with higher MDS-UPDRS III at admission, lower age, and less depression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This corresponds to an absolute reduction of −9.55 points, which is above the minimal clinically important difference for improvement of −3.25 points and is correspondingly clinically significant [ 11 ]. This is in line with earlier studies showing improvement of motor function after PD-MCT [ 4 , 5 , 6 ]. We found that improvement of MDS-UPDRS III after PD-MCT in patients with PD is more likely to occur in patients with higher MDS-UPDRS III at admission, lower age, and less depression.…”
Section: Discussionsupporting
confidence: 93%
“…In Germany, the majority of patients are treated for at least 14 days (OPS8-97d.1) [ 3 ]. The longer treatments (OPS8-97d.1 and OPS8-97d.2) have a positive effect on motor and nonmotor symptoms, as shown in two smaller nonrandomized studies with 126 and 47 PD patients [ 4 , 5 , 6 ]. Only one of the two studies also analyzed whether this positive effect persisted after hospital discharge in a follow-up examination of 47 patients after six weeks [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The Multimodal Complex Treatment is an in-patient treatment program geared towards more advanced patients and very complicated cases. The treatment compromises on average, fourteen days of in-patient care with a multimodal assessment at the beginning and end [ 26 , 27 ]. Patients receive at least 7.5 h of therapy per week by various therapists, specifically tailored to their needs.…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to the application of the composite clinical motor score in routine clinical practice include the necessity to measure all three constituents (MDS-UPDRS III, Purdue Pegboard Test and TUG); of questionable feasibility considering typical time constraints, though used by a number of research studies to date 22 44. Refinement of the composite clinical motor score, through the identification and exclusion of redundant constituents or their subitems, may be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%